Ethnobotanical, Phytochemical, and Pharmacologies Aspect of Kaempferia rotunda L. as a Local Herbal Plant with Global Potential: A Review - Pujiyanti, Aloysia Sri; Kusuma, Ratna; Ilmi, Annisa Nurul; Hasibuan, Febry Rahmadhani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Kaempferia rotunda L., also known as kunci pepet, is a local herbal plant with global potential traditionally used in various medicinal practices across Southeast Asia. This review summarizes the ethnobotanical, phytochemical, and pharmacological aspects of Kaempferia rotunda L., to explore its applications in modern medicine. Ethnobotanically, its rhizome has been widely utilized for treating digestive disorders, inflammation, and wound healing. Phytochemical studies reveal that Kaempferia rotunda L., contains flavonoids, alkaloids, phenols, and terpenoids, contributing to its biological activities. Several studies have demonstrated significant anti-inflammatory, antibacterial, antioxidant, and anticancer properties. With the increasing demand for natural-based therapies, further exploration of their active compounds and mechanisms of action is highly relevant. This review aims to provide a broader insight into the pharmaceutical potential of Kaempferia rotunda L., and encourage further research for the development of evidence-based herbal medicine.